If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 56 + -16x = -9x Solving 56 + -16x = -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 56 + -16x + 9x = -9x + 9x Combine like terms: -16x + 9x = -7x 56 + -7x = -9x + 9x Combine like terms: -9x + 9x = 0 56 + -7x = 0 Add '-56' to each side of the equation. 56 + -56 + -7x = 0 + -56 Combine like terms: 56 + -56 = 0 0 + -7x = 0 + -56 -7x = 0 + -56 Combine like terms: 0 + -56 = -56 -7x = -56 Divide each side by '-7'. x = 8 Simplifying x = 8
| 7(9d+8)=28 | | X(7x+5)=180 | | 3-3(-2b+2)=4(b-4)+3 | | 5x-10=12.5 | | 3p+9=0 | | 8-3(p-a)=2p | | 27=4p-9 | | -5-13=8x+17-7x | | h(-10)= | | 14/541n-454r | | -4x+9+5x=-10+7 | | X=3+-2 | | M(6x+5)=180 | | -18+7+(-3)=x | | 5(-.8+.4y)+4y=20 | | X-0.8=5.4 | | y^6-2y^3+y=0 | | 3/8=1/4p | | 5*-.8= | | x-8x+16=13 | | -15x-15y= | | 2(-2b+2)=-3(-4+b) | | 12x=-12+36 | | 3(2x+12)=-s(x-4)+x | | 0.03(m+7)=0.002(5-m)+0.03 | | 20x+15x-20(x-1)-15(x-1)=245 | | F(x)=-0.5x^3+3x^2+0.5x-15 | | 6q-10=20 | | X-(-13)=-6 | | 7(x-7)+9=4(x-7) | | 12a+19a+15= | | 4x+3=-4+2x+25 |